A novel Alaska pollack-derived peptide, which increases glucose uptake in skeletal muscle cells, lowers the blood glucose level in diabetic mice. Issue 8 (5th August 2015) - Ayabe, Tatsuhiro; Mizushige, Takafumi; Ota, Wakana; Kawabata, Fuminori; Hayamizu, Kohsuke; Han, Li; Tsuji, Tomoko; Kanamoto, Ryuhei; Ohinata, Kousaku
<x xml:space="preserve">Abstract</x> We found that the tryptic digest of Alaska pollack protein (APP) and novel APP-derived peptide exhibited a glucose-lowering effect in KK-Ay mice, a type II diabetic mice.